Analisis Cost Benefit pada Edukasi Penerapan Konsep 5S Produksi Mukena di Konveksi Roemah Dia - Widiyarini, Widiyarini; Rosalina, Uki Aulia; Perdana, Surya (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to improve work efficiency and productivity through the education and implementation of the 5S concept (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) in the production process of mukena at Roemah Dia Convection. The method consisted of observation, interviews, socialization, and cost–benefit analysis (CBA). The results indicated a significant improvement in workers’ awareness of workplace cleanliness, orderliness, and discipline. Economically, the implementation cost was IDR 3,760,000, generating a benefit value of IDR 6,000,000, resulting in a CBA ratio of 160%. This indicates that the 5S implementation is both feasible and profitable since the benefits outweigh the costs. In addition to financial gains, this program also enhanced worker motivation, comfort, and time efficiency. Therefore, the application of the 5S concept proves to be an effective strategy to improve performance and productivity among small and medium-scale garment enterprises in Indonesia.